Powder-Based 3D Printed Porous Structure and Its Application as Bone Scaffold - Zhao, Yingchun; Hou, Yue; Li, Zhaoyu; Wang, Ziyu; Yan, Xinxin (Frontiers in Materials, 2020)
Customized porous structures are widely used in bone tissue engineering as bone substitutes. In natural bone, the bone tissue relies on blood vessels in vesicular structure for nutrition supply. When a defect appears, the biomimetic porous scaffold becomes a good candidate for new blood vessels formation and helps the bone tissue ingrowth. To construct an osteoconductive bone scaffold that is suitable for the defect region, the powder-based 3D printing technology holds great promise since they can deal with biocompatible and biodegradable materials. In this mini review, we introduce several types of powder-based manufacturing technologies and their corresponding printable materials for the construction of porous structures. Besides some research cases are highlighted to illustrate the recent development of some research directions related to the bone scaffold for bone tissue regeneration.